Correlation Of Parents' Level Of Knowledge With Actions Against Refractive Directness In Children Aged 5 – 8 Years At State Primary School - Siregar, Okkis Razuansyah; Sari, Siti Kemala; Kosasih , Edward (Jurnal Perilaku Kesehatan Terpadu, 2023)
Refractive errors are the third most common cause of blindness. Uncorrected refractive errors in children will disrupt their learning process. Good parental knowledge and action regarding disorders will be able to prevent vision problems in children. This study aims to study the correlation between parents' level of knowledge and actions regarding refractive errors in children. The design of this research is cross sectional analytic. The sample for this research was parents of students at SD Negeri 101751 Klambir V grades 1 and 2. The sample size was 61 respondents. The sampling technique used simple random sampling. The instrument used in the research was a questionnaire. The data obtained was tested using Spearman analysis. The results of this study show that there is a significant correlation between the level of parental knowledge and actions regarding refractive errors in children with a value of p < 0.05 (p = 0.000). The close relationship between variables is moderate with a value of r=0.478. The level of parents' knowledge of refractive errors is significantly related to their actions. It is hoped that there will be a promotional program from the health department to provide education or counseling regarding eye health, and visual acuity screening, for early detection of refractive errors in children.